PELATIHAN BAHASA MANDARIN DASAR DI SMP 163 JAKARTA - elyana elyana (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
This activity took place at 163 Junior High School which located at Jl. Empang Tiga, RT.8/RW.2, Pejaten Timur, Kec. Ps.Minggu, City of South Jakarta, Capital Region of Jakarta 12510. This activity was carried out online using the Zoom application. it was held for four weeks starting on November 13 to December 4, 2021, one meeting each week -which aims to introduce Mandarin language -and to provide knowledge to the participants. The method used in this activity is based on theory as well as practice, like classroom action research using 4 stages, which are namely planning, implementation, reflection and reporting. The results obtained from this activity are that students can recognize basic Mandarin, understand Chinese vocabulary and simple conversations, such as introducing them selves using Mandarin. In this activity the participants were very enthusiastic and the results obtained were that participants were able to know What are initials and finals in Mandarin nderstand how to say and use simple sentences, like greetings and introduce themselves in Mandarin with proper pronunciation